(untitled) (Sahayaatra सहयात्रा, 2026)
This study examines whether Nepal’s Social Security Allowance (SSA) can remain financially sustainable in the long run. It mainly focuses on the connection between increasing life expectancy and the age at which people start receiving benefits. Since the program was introduced in 2051/52 (1994/95), Nepal has gone through noticeable demographic changes. Life expectancy has increased from 58 years to 73 years. However, the age for receiving SSA has been reduced from 75 to 68 due to Government changes. Because of this, many people start getting benefits earlier than the average life expectancy. For this study, 30 years of data are reviewed, including government budgets, number of beneficiaries, and key economic indicators. The findings show that government spending on SSA has grown very fast, rising from NPR 375.60 million to NPR 115 billion. This increase has created pressure on public finance. The share of SSA expenditure relative to GDP is also rising, raising questions about sustainability. The analysis also suggests that lowering the eligibility age is closely linked with increasing the financial burden of the country. The current eligibility age of 68 years may not be sustainable over time, especially if the government needs to invest in other development areas. Therefore, this study suggests raising the eligibility age to 75 years. This change may help control expenses and ensure that support reaches the most vulnerable elderly population.